Antifungal activity of essential oils associated with edible coatings for the postharvest control of spoilage fungi in strawberry (Fragaria spp.) - Oliveira, Jacqueline de (2019)
Strawberry cultivation presents as limiting problem the phytosanitary management, which, associated with the residues of the toxic fungicides, the resistance of pathogens and the fragility of the fruit during transport and storage, make the commercialization of this product a challenge. The identification and development of new products with antifungal action, such as essential oils (EOs), is a promising alternative. Therefore, the present study addresses: the in vitro antifungal activity of three essential oils, Eucalyptus staigeriana, Lippia sidoides and Pimenta pseudocaryophyllus; the chemical composition and the mode of action of the EO with the highest potential and its in vivo activity when associated with carboxymethylcellulose (CMC), as well as its effects on the sensory quality and postharvest of strawberries. In chapters two, three and four, the studies were directed to Colletotrichum acutatum, Rhizopus stolonifer and Botrytis cinerea, respectively. In the last chapter, the antifungal activity of a commercial, alternative formulation with low toxicity was evaluated against the same three pathogens. Among the EOs evaluated, the one from L. sidoides presented the best antifungal activity, with the predominance of thymol in its composition, causing morphological alterations in the pathogens. in vivo, the strawberries treated with CMC associated to the EO presented a reduction in the severity of the diseases and improvements in the physicochemical properties with little alteration in the sensory quality of the fruit. The commercial formulation also presented a potential for the control, in vitro and in vivo, of the main postharvest strawberry-deteriorating fungi.